REALIZATION OF THE LINGUISTIC AND METHODOLOGICAL POTENTIAL OF AN AUTHENTIC TEXT WHEN TEACHING ENGLISH ARTICLES (Intent Research Scientific Journal, 2023)
This article discusses the problem of improving the grammatical skill of using articles when learning English at an advanced level in secondary school on the basis of an authentic text. The author defines the object, subject, purpose, as well as the objectives of the study. Then the basic concepts of scientific work are revealed: skill, grammatical skill, article, authentic text. The linguistic and methodological potential of using authentic text in teaching articles is substantiated, its main types are listed, criteria for assessing its authenticity are highlighted, and the main advantages of its use in English lessons are outlined. A way to solve the problem with the help of an authentic text as a means of teaching articles is proposed.